(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Information and Communication Technologies (ICT) are a concept that is constantly evolving over time. In many cases, the Internet has been the driving force behind the continuous growth of various learning resources and objects developed through computer tools and software, which provide support in educational processes. This article seeks to provide a reflection that allows us to situate ourselves in a specific temporal and spatial context. The aim is to analyze whether the user experience, known as User Experience (UX), is related to instructional design in the field of technopedagogy, and if it really adapts to the needs of students. Based on categorization, coding and triangulation through Atlas.ti, a theoretical approach to the meanings and meanings of instructional design was carried out from the perspective of social actors. In this way, from UX considerations, it is important to know the perception and attitude of the instructional designer in order to interpret the pedagogical processes immersed in online education systems, platforms, courses or even specific learning resources so that We can think about how to implement management processes to create, develop and continually improve resources that support the teaching-learning process. Research has confirmed that UX plays a fundamental role in the effectiveness of techno-pedagogical resources. Instructional designers recognize the importance of providing a positive and accessible user experience.